The Effort Of Performance Optimization With Basic Design Of Revitalization For Treatment Instalation Of Waste Water Cisirung, South Bandung - Adiana, Ratna; Hidayat, Ratna; Yusuf, Iskandar A; Misbahudin, Misbahudin; Taufiq, Ahmad (JURNAL SUMBER DAYA AIR, 2018)
In relation to the efforts of restoration and water pollution control (PPA) into the upstream Citarum River, the revitalization of IPAL Cisirung is done to increase the capacity to optimize its performance. IPAL Cisirung is built with wastewater, chemical and biological waste treatment technology. This activity is carried out by conducting field survey and sample testing in the laboratory. The current wastewater discharge that goes to IPAL Cisirung is 206,10 L/sec. The purpose of this activity is to make basic design of IPAL Cisirung revitalization as reference of Detail Engineering Design (DED) with planning capacity of 350 L/sec. Water sampling is done based on the description of the processing unit that must be revitalized, namely equalization tub, sedimentation bed outlet I and sedimentation basin II. The result of laboratory test showed that the optimum condition of turbidity was 28.6 NTU. Revitalization of the biological treatment unit is designed using the Moving Bed Biofilm Reactor (MBBR) technology. The advantages are very effective in reducing COD by 85%, reducing nitrogen through nitrification process and able to absorb TSS or MLSS as much as 2400 mg/L.